(untitled) (Research, Society and Development, 2025)
Objectives: Leishmaniasis is a neglected tropical zoonosis that manifests in forms ranging from cutaneous to visceral. The objective of this study is to analyze the epidemiological profile of leishmaniasis in the state of Minas Gerais and to propose interventions for the region based on a systematic review. Methods: This is an epidemiological study that uses data from the Mortality Information System (SIM) from 2018 to 2022, describing deaths caused by leishmaniasis in Minas Gerais. In addition, a systematic literature review was conducted using the PubMed, Cochrane, and Embase databases. The review included systematic review articles from the last five years that addressed intervention, control, or prevention of leishmaniasis, excluding studies with primary data and duplicates. Results: A total of 157 deaths from the disease were recorded in the state. The most affected groups were males (66.88%), individuals of mixed-race and Black ethnicity (73%), and the elderly (48%). Although deaths were concentrated in the state capital, most victims were originally from cities in the northern and northeastern regions of the state and were also associated with rural labor. The literature review identified 11 articles that supported the proposed intervention strategy focused on vector control, community empowerment, and intersectoral collaboration among public authorities. Conclusion: Underreporting deaths was observed due to the COVID-19 pandemic. Additionally, regions less affected by the disease had higher household incomes. As for interventions, the main strategies include reducing social vulnerability in rural areas, opening Primary Health Care Units, promoting health education, and combating the vector mosquito.